Pile-Sleeve Strength Modelling in API RP2A WSD, LRFD and ISO 19902 - Sambu Potty, Narayanan (2010)
Malaysia has been using API RP2A WSD for design of offshore platforms. Many countries have embraced the probability based design through the use of the LRFD method. Due to this and many other factors, it is essential to adopt the LRFD methodology. When adopting this methodology, the appropriate load and resistance factors can be optimised through the process of calibration. The first step in the calibration process is the determination of reliability of structural elements and joints of the jacket designed as per existing practice. The designs using the new LRFD expressions should have the same reliability. To determine the resistance factors for the pile sleeve joints, knowledge of the relevant strength equations in the different codes and the similarities and differences between them are useful. The pile sleeve strength equations for plain joints and joints with shear keys are reviewed. Information in literature that form the background to the code provisions are also reviewed and presented.